1998
DOI: 10.1183/09031936.98.12061397
|View full text |Cite
|
Sign up to set email alerts
|

Loss of immunoreactivity for RTI40, a type I cell-specific protein in the alveolar epithelium of rat lungs with bleomycin-induced fibrosis

Abstract: The rat alveolar epithelium comprises three different epithelial cell types: the large squamous type I cells, the cuboidal type II pneumocytes and the bottle-shaped alveolar brush (type III) cells. Various biochemical markers have been used to distinguish type I from type II cells. Most of these markers are not unique for either cell type, but are helpful in defining the different phenotypes of type I and type II cells. Type II pneumocytes may be distinguished from type I cells by their cytokeratin pattern, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 20 publications
2
22
2
Order By: Relevance
“…It also showed cellular hyperplasia, enhanced matrix deposition, and abnormal interstitial cells proliferation. In accordance with the study by Koslowski et al, 29 the in vivo imaging and the ex vivo immunofluorescence showed areas of variable RTI40 protein staining at the alveolar surface (from no to irregulardiscontinuous labeling, with foci of 'normal' or already restored alveolar epithelium) 3 weeks following bleomycin administration. In this regard, taking into consideration that the dose of bleomycin I/T instilled was mild (1.5 vs 7 TU per rat 30 ) and though several brown areas were obviously visible macroscopically, IgGs were topically applied and should not normally have accessed nonatelectatic open airways and Lung in vivo endomicroscopy F Chagnon et al spaces in vivo (ie, less injured areas), whereas they will have contacted these tissues in ex vivo fixated samples.…”
Section: Discussionsupporting
confidence: 90%
“…It also showed cellular hyperplasia, enhanced matrix deposition, and abnormal interstitial cells proliferation. In accordance with the study by Koslowski et al, 29 the in vivo imaging and the ex vivo immunofluorescence showed areas of variable RTI40 protein staining at the alveolar surface (from no to irregulardiscontinuous labeling, with foci of 'normal' or already restored alveolar epithelium) 3 weeks following bleomycin administration. In this regard, taking into consideration that the dose of bleomycin I/T instilled was mild (1.5 vs 7 TU per rat 30 ) and though several brown areas were obviously visible macroscopically, IgGs were topically applied and should not normally have accessed nonatelectatic open airways and Lung in vivo endomicroscopy F Chagnon et al spaces in vivo (ie, less injured areas), whereas they will have contacted these tissues in ex vivo fixated samples.…”
Section: Discussionsupporting
confidence: 90%
“…B. purpurea agglutinin) but demonstrate focal loss of RTI 40 / TIa protein [94]. Other investigations into lung fibrosis also report the loss of ATI-cell-associated proteins, including caveolin-1, RTI 40 /TIa protein, AQP5 and RAGE [30,95,114].…”
Section: Alveolar Epithelial Type I Cell-selective Proteins and Lung mentioning
confidence: 87%
“…In contrast, in a model of focal ATI cell necrosis, induced by nitrogen dioxide exposure, BALF concentrations of RTI 40 / TIa protein are elevated only two-fold above control values and alveolar fluid clearance is stimulated [90]. BALF RTI 40 / TIa protein concentrations are also elevated, to varying degrees, in other acute injury models, including hyperoxia [91], Staphylococcus aureus-induced pneumonia [92], acidinstillation followed by ventilator-induced injury [96] and following intratracheal adminstration of bleomycin (table 2) [94]. In the rat model of acid-instillation, RTI 40 /TIa protein concentrations in oedema fluid and plasma were significantly reduced in animals ventilated at low tidal, or protective, volumes in comparison with those ventilated at higher tidal volumes (i.e.…”
Section: Expression Of Alveolar Epithelial Type I Cell-selective Protmentioning
confidence: 99%
“…For detection of the type I pneumocyte-specific protein rat type I cell marker (RTI40) in the BALF, proteins were sedimented by centrifugation for 2 h at 100,0006g at 4uC, as described previously [2]. Proteins were redissolved in 360 mM tris-(hydroxymethyl)-aminomethane (Tris)/HCl (pH 6.8) containing 190 mM sodium dodecyl sulphate (SDS), 0.03% bromophenol blue and 55% glycerol (volume/volume) and incubated for 5 min at 95uC.…”
Section: Western Blottingmentioning
confidence: 99%
“…Intratracheal administration of bleomycin into the lung of rats causes a sequence of morphological and biochemical changes, such as acute inflammation with oedema and damage to the alveolar epithelium as well as influx of inflammatory cells. Finally, a phase of chronic injury, which is characterised by tissue remodelling with proliferation of fibroblasts and pneumocytes and thickening of the alveolar walls, follows [1][2][3]. This fibrotic process is accompanied by excessive production and accumulation of connective tissue components.…”
mentioning
confidence: 99%